MYBL2 guides autophagy suppressor VDAC2 in the developing ovary to inhibit autophagy through a complex of VDAC2-BECN1-BCL2L1 in mammals - Yuan, Jia (Autophagy, 2015)
Oogenesis is essential for female gamete production in mammals. The total number of ovarian follicles is determined early in life and production of ovarian oocytes is thought to stop during the lifetime. However, the molecular mechanisms underling oogenesis, particularly autophagy regulation in the ovary, remain largely unknown. Here, we reveal an important MYBL2-VDAC2-BECN1-BCL2L1 pathway linking autophagy suppression in the developing ovary. The transcription factors GATA1 and MYBL2 can bind to and activate the Vdac2 promoter. MYBL2 regulates the spatiotemporal expression of VDAC2 in the developing ovary. Strikingly, in the VDAC2 transgenic pigs (Sus scrofa/Ss), VDAC2 exerts its function by inhibiting autophagy in the ovary. In contrast, Vdac2 knockout promotes autophagy. Moreover, VDAC2-mediated autophagy suppression is dependent on its interactions with both BECN1 and BCL2L1 to stabilize the BECN1 and BCL2L1 complex, suggesting VDAC2 as an autophagy suppressor in the pathway. Our findings provide a functional connection among the VDAC2, MYBL2, the BECN1-BCL2L1 pathway and autophagy suppression in the developing ovary, which is implicated in improving female fecundity.